A multidimensional approach to Spanish–English bilingual preschoolers' narrative skills (Un enfoque multidimensional de las habilidades narrativas de los niños preescolares bilingües inglés/español). Issue 2 (3rd April 2021) - Shiro, Martha; Hoff, Erika
ABSTRACT: We identify language and discourse skills in 54-month-old Spanish–English bilingual preschoolers and their English-speaking monolingual peers, using multiple measures. Forty-one Spanish–English bilingual and 25 English monolingual children, all US born, viewed an eight-minute wordless video. The bilingual children recounted the story once in English and once in Spanish, in counterbalanced order. The story retellings were transcribed and coded for discourse skills (narrative length, narrative components and uses of evaluative language) and language skills (number of words, number of different words, MLUw). No difference was found in the two groups´ overall language or discourse skills, assessed in the narrative production, with the exception of certain uses of evaluative language. Within the bilingual group, all measures, except MLUw, were highly correlated across the two languages. Our multidimensional analysis of narrative structure and use of evaluative language sheds light on certain differences between the ways in which English monolinguals and Spanish–English bilinguals organize their narrative discourse. We discuss the advantages of using this multidimensional approach in assessing bilinguals´ language and discourse abilities in narrative production.